Produtividade da palma forrageira cv. orelha de elefante mexicana sob diferentes sistemas de irrigação e frequências de corte - Reis Filho, Raimundo José Couto dos (2020)
The objective of this study was to evaluate the effect of the use of different irrigation systems and cutting frequencies in the cultivation of cactus pear. The research was carried out in the Semiarid region, in the city of Russas, in the state of Ceará, Brazil. The experimental design used was of randomized blocks in subdivided plots, with four irrigation methods and four cutting frequencies, with four replications. The plots were represented by irrigation systems (surface drip, micro sprinkler, micro spray jet and conventional sprinkling) and subplots by cutting frequency (6, 9, 12 and 18 months). The spacing used was 1.60 m x 0.40 m x 0.14 m, which provided a density of 70,000 plants ha-1. The execution period of the experiment was from December 2016 to January 2019. Regarding irrigation management, a two-day irrigation shift was defined, using a gross water sheet of 5.0 mm (2.5 mm.day-1), a management established equally for all evaluated irrigation systems. Morphometric and productive variables and water relations of the cactus pear cv. Orelha de Elefante Mexicana (Opuntia stricta (Haw.) Haw.) were evaluated. The cut-off frequency and irrigation system factors influenced most of the evaluated morphological and productive characteristics. It was observed that the increase in the cutting frequency showed a positive linear effect for the variables: final plant height, number of 1st order cladodes and dry mass production of 2nd and 3rd order cladodes. It also showed a positive linear effect in the cladodes area index, with the highest observed at the cut-off frequency of 18 months (2.23 m2/m2), a result that differed statistically (P<0,01) from the values obtained in the cutting frequencies of 6 months (1.24 m2/m2), 9 months (1.30 m2/m2) and 12 months (1.78 m2/m2). The cut-off frequency of 18 months presented the highest values for the percentage of the plant’s dry matter. On the other hand, the cut-off frequency of 6 months presented the lowest values for length, width and thickness of 2nd order cladodes, number of 3rd order cladodes, number of harvestable cladodes, average weight of 2nd order cladodes and dry mass production of 2nd order clade. Regarding the effect of the cutting frequency on water use efficiency (WUE), the highest values for fresh mass production were obtained at the frequencies of 6 and 12 months, 134.19 and 108.62 kg of MFha-1 mm-1, respectively. For water use efficiency for dry mass, the highest value was obtained at the frequency of 6 months, 8.46 kg DMha-1 mm-1. Regarding irrigation systems, conventional sprinkling presented better results, for most morphological and productivity variables evaluated. This system obtained the highest cladodes area index, 2.05 m2/m2, presenting significant difference (P<0,01) for the values observed in the micro spray jet systems (1.67 m2/m2), microsprinkler (1.55 m2/m2) and surface drip (1.28 m2/m2). Conventional sprinkling also showed the highest values of number of 2nd order clade (4.92 plant cladodes-1), fresh mass production of 2nd order cladodes (121.57 t FMha-1 year-1) and total fresh mass production rate (548.12 kg ha-1 day-1). The conventional sprinkling system and micro spray jet showed the highest values for number of 1st order cladodes, number of cladodes of the plant, number of harvestable cladodes, rate of production of fresh mass of cladodes of 3rd order, dry mass production of 2nd and 3rd order cladodes and dry mass production rate of 2nd and 3rd order cladodes. The cut-off frequency of 12 months associated with the conventional sprinkler system presented the highest yields of fresh mass of third-order cladodes (86.48 t FMha-1) and total cladodes (267.79 t FMha-1), and higher total dry mass production (16.37 t DMha-1) and total dry mass production rate (44.86 kg MSha-1 day-1). The highest water use efficiency values for fresh mass production occurred in the conventional sprinkler system, 128.56 kg of FMha-1 mm-1, while for water use efficiency for dry matter production, the highest values were obtained in conventional spray (8.20 kg DMha-1 mm-1) and micro spray jet (6.89 kg DMha-1 mm-1). No plant mortality was observed, evidencing the rusticity and adaptability of the cv. Orelha de Elefante Mexicana (Opuntia stricta (Haw.) Haw.) in irrigated regime, regardless of the cutting frequency and irrigation systems used. The conventional sprinkler system and the cut-off frequency of 12 months presented the best results, and these can be adopted as a strategy of irrigated and thickening cultivation of cactus pear cv. Orelha de Elefante Mexicana (Opuntia stricta (Haw.) Haw.).